Advantages of Hybrid Organising in Social Entrepreneurship: Evidence from Norway - Mitra, Paulimi; Byrne, Janice; Janssen, Frank (Senate Hall, 2017)
Hybrid organising within the context of social entrepreneurship has been on the rise. At the same time, social entrepreneurial ventures that adopt hybrid organising are often criticized. The literature on hybridity points to particular challenges for social entrepreneurial ventures such as conflicting institutional logics and tensions related to their dual identity and/or mission drift. Drawing on the literature on hybrid organising and social entrepreneurship, in this paper we take a contrary stance and explore the positive aspects of hybrid organising in social entrepreneurship. We ask the following research question: "What are the advantages of hybrid organising in social entrepreneurship, if any"? Using a qualitative approach, this study theorizes two main advantages of hybrid organising: sustainability of the organisational model and efficiency of the organisational model. The article also discusses the implications for theory and practice.
Keywords: social entrepreneurship|hybrid organising|advantages of hybridity